Rab GTPases: Central Coordinators of Membrane Trafficking in Cancer - Jin, Hongyuan; Tang, Yuanxin; Yang, Liang; Peng, Xueqiang; Li, Bowen; Fan, Qin; Wei, Shibo; Yang, Shuo; Li, Xinyu; Wu, Bo; Huang, Mingyao; Tang, Shilei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Tumour progression involves invasion, migration, metabolism, autophagy, exosome secretion and drug resistance. Cargos transported by membrane vesicle trafficking underlie all of these processes. Rab GTPases, which, through coordinated and dynamic intracellular membrane trafficking alongside cytoskeletal pathways, determine the maintenance of homeostasis and a series of cellular functions. While mutations in Rab GTPases may not be direct drivers of cancers, the mechanism of vesicle movement plays essential roles in cancers. Therefore, targeting Rab GTPases to adjust membrane trafficking has the potential to become a novel way to adjust cancer treatment. In this review, we describe the characteristics of Rab GTPases; in particular, we discuss the role of their activation in the regulation of membrane transport and provide examples of Rab GTPases regulating membrane transport in tumour progression. Finally, we discuss the clinical implications and the potential as a cancer therapeutic target of Rab GTPases.